Solutions of the Dirac Equation for the Quadratic ExponentialManning-Rosen Potential plus Yukawa Potential within theYukawalike Tensor Interaction using the Framework of Nikiforov-Uvarov Formalism - Louis, Hitler; Benedict, Ita I.; Nelson, Nzeata I.; Chidinma, Ike V. (Jordan Journal of Physics, 2025)
Here, we solve the Dirac equation for the quadratic exponential-type potential plus Manning-Rosen potential including a Yukawa-like tensor potential with arbitrary spinorbit coupling quantum number κ. In the framework of the spin and pseudo-spin (pspin) symmetry, we obtain the energy eigenvalue equation and the corresponding eigenfunctions in closed form by using the Nikiforov–Uvarov method. Also, special cases of the potential have been considered and their energy eigenvalues as well as their corresponding eigenfunctions were obtained for both relativistic and non-relativistic scope. Keywords: Dirac equation, Quadratic exponential-type potential, Manning-Rosen potential, Spin and pseudospin symmetry, Nikiforov-Uvarov method.